35 Manual versus semi-automatic rhythm analysis and defibrillation for out-of-hospital cardiac arrest. (21st May 2017) - Nehme, Z; Andrew, E; Nair, R; Bernard, S; Smith, K
Abstract : Aim: Although manual and semi-automatic external defibrillation (SAED) are commonly used in the management of cardiac arrest, the optimal strategy is not known. We hypothesised that SAED would reduce the time to first shock and increase survival compared to a manual strategy. Methods: Between 2005 and 2015, we included adult out-of-hospital cardiac arrests (OHCA) of presumed cardiac aetiology. On October 2012, a treatment protocol utilising SAED was introduced following years of manual defibrillation by paramedics. The effect of SAED implementation on patient outcomes was assessed using adjusted interrupted time series models. Results: Of the 14 776 cases, 10 224 (69.2%) and 4552 (30.8%) occurred during the manual and SAED protocols, respectively. After adjustment for arrest confounders and temporal trend, the odds of delivering the first shock within 2 min of arrival increased under the SAED protocol (adjusted odds ratio [AOR] 1.72, 95% CI: 1.32, 2.26; p<0.001). Despite this, the SAED protocol was associated with a reduction in return of spontaneous circulation (AOR 0.81, 95% CI: 0.68, 0.96; p=0.01), event survival (AOR 0.74, 95% CI: 0.62, 0.88; p=0.001) and survival to hospital discharge (AOR 0.71, 95% CI: 0.55, 0.92; p=0.009) when compared with the manual protocol. Although SAED reduced the time to first shock, there was no improvement in the rate of successful first shock cardioversion (AOR 0.73, 95% CI: 0.51, 1.06; p=0.10). Conclusion: Although SAED improved the time to first shock, this did not translate into higher rates of successful cardioversion or survival for OHCA patients. Advanced life support providers should be trained in a manual defibrillation protocol. Conflict of interest: None declared. Funding: None declared.